Deskription und Bewertung strukturierter Produkte unter besonderer Berücksichtigung verschiedener Marktszenarien - Andreas Löhr; Heinz Cremers (Frankfurt School of Finance & Management, 2007)
Due to a fast market development in volume and innovation on the structured products (certificates) side, critics are finding fault regarding a lack in transparency and comparability. However, certificates can provide characteristics for every market scenario as its explicit strength. The aim of the following working paper is to provide transparency and an analysis in the most common certificates. The analysis consists of a description, valuation and scenario analysis which then leads to a substantial overview and should provide knowledge which certificate can be used in specific market scenarios.
urn:nbn:de:101:1-20080827295
Keywords: 330; Financial engineering; strukturierte Produkte; Zertifikate; evaluation by duplication; Discountzertifikate; Aktienanleihe; Doppel-Aktienanleihe; Cheapest-to-deliver-Zertifikat; Bonus-Zertifikat; Sprint-Zertifikat; Outperformance-Zertifikat; Reverse Sprint-Zertifikat; Reverse Outperformance-Zertifikat